Deforestation and malaria incidence in the legal Amazon Region between 1996 and 2012 - Raphael Mendonça Guimarães; Bárbara Campos Valente; Priscila Almeida Faria; Lásaro Linhares Stephanelli; Juliana Valentim Chaiblich; Felipe Bagatoli Silveira Arjona (Cadernos de Saúde Coletiva, 2016)
Abstract Malaria is a major public health problem, and Brazil is the largest contributor in America to the number of cases. In the country, the Amazon concentrates around 99.5% of the cases. This article aims to compare trends in deforestation rate and the parasite index of malaria in the Amazon region between 1996 and 2012. The annual crude rate of deforestation and the Annual Parasite Index (API) of malaria between 1996 and 2012 were estimated. The rate of deforestation has great variability among the states every year, and a similar situation is observed for malaria API over the studied period. There are important variations across the states within this period. The historical series of crude deforestation rate and malaria API have markedly similar trends; with a 1-2 years lag between them, suggesting that the occurrence of fluctuations in deforestation numbers impacts malaria numbers in a period immediately following. The mapping of deforested areas and the analysis of temporal series are therefore useful in the analysis of malaria.